2001
DOI: 10.1093/jn/131.11.2910
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Bisphosphonate Ibandronate Prevents Vitamin D Toxicity and Inhibits Vitamin D-Induced Calcification of Arteries, Cartilage, Lungs and Kidneys in Rats

Abstract: Experiments were carried out to determine whether the doses of the amino bisphosphonate ibandronate that inhibit bone resorption inhibit soft tissue calcification and death in rats treated with a toxic dose of vitamin D. These studies were prompted by the recent discovery that ibandronate doses that inhibit bone resorption potently inhibit artery calcification induced by treatment with the vitamin K antagonist warfarin. All 16 rats treated with the toxic dose of vitamin D (12.5 mg cholecalciferol x kg(-1)) die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 20 publications
5
99
0
Order By: Relevance
“…Unfortunately, vitamin D may predispose to vascular calcification. Rats that were treated with high-dose vitamin D developed calcification in the aorta, carotid, hepatic, mesenteric, renal, and femoral arteries (26). Clinical studies have also reported an association between vascular calcification and use of vitamin D therapy in hyperphosphatemic patients with renal failure (27,28).…”
Section: Control Of Secondary Hyperparathyroidism: Vitamin D Versus Cmentioning
confidence: 99%
“…Unfortunately, vitamin D may predispose to vascular calcification. Rats that were treated with high-dose vitamin D developed calcification in the aorta, carotid, hepatic, mesenteric, renal, and femoral arteries (26). Clinical studies have also reported an association between vascular calcification and use of vitamin D therapy in hyperphosphatemic patients with renal failure (27,28).…”
Section: Control Of Secondary Hyperparathyroidism: Vitamin D Versus Cmentioning
confidence: 99%
“…(15) Agents that enhance bone quality also reduce cardiovascular calcification. (16)(17)(18)(19)(20)(21)(22)(23) Additionally, soft-tissue calcification including vascular calcification is a common feature of genetic mouse and rat models harboring defects associated with bone mineralization. (24)(25)(26) Clinical improvements in bone health, regardless of the initial bone defect, ameliorate progression of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…In general, crystallization inhibitors bind to the crystal nucleus or to the crystal face and hence prevent or disturb crystal development without any cellular signaling capacity. Pyrophosphate, 28 bisphosphonates (such as etidronate, alendronate and ibandronate) [29][30][31] and phytate (myoinositol hexakisphosphate) 32 have been shown to inhibit crystallization in the form of vascular calcification. Etidronate is used to treat osteoporosis, 33 and phytate is a naturally occurring compound that can either be ingested 34,35 or absorbed topically.…”
mentioning
confidence: 99%